A model for the Schottky anomaly in metallic Nd2-yCeyCuO4 - Lagos, R. E.; Stein-Barana, ACM; Cabrera, G. G. (Elsevier B.V., 1998)
We present a simple model for the doped compound Nd2-yCevCuO4, in order to explain some recent experimental results on the latter. Within a Hartree-Fock context, we start from an impurity Anderson-like model and consider the magnetic splitting of the Nd-4f ground state Kramers doublet due to exchange interactions with the ordered Cu moments. Our results are in very good agreement with the experimental data, yielding a Schottky anomaly peak for the specific heat that reduces its amplitude, broadens and shifts to lower temperatures, upon Ce doping. For overdoped compounds at low temperatures, the specific heat behaves linearly and the magnetic susceptibility is constant. A smooth transition from this Fermi liquid-like behavior occurs as temperature is increased and, at high temperatures, the susceptibility exhibits a Curie-like behavior. Finally, we discuss some improvements our model is amenable to incorporate, (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: Schottky anomalies; rare earths; Anderson model; cuprate oxides